RADIOACTIVE MINERAL PROSPECTING USING LANDSAT-8 AND ROCK/SOIL RADIOMETRIC IN MAMUJU REGION, WEST SULAWESI - Dian Indrastomo, Frederikus
Environmental radioactivity measurements conducted by PTKMR-BATAN in 2007 in West Sulawesi region was showing high radioactivity dose rate (100- 2,800 nSv/h). High radioactivity dose rate is commonly occurred from high concentration of potassium (K), uranium (U), and thorium (Th) in nature. This high dose rate was found in Adang volcanic rocks. Volcanic morphologies are commonly had a steep slope and high elevation. These conditions make difficulties in collecting ground data. Remote sensing application with regional rock/soil radioactivity measurements are helping tools to know mineralization control of U and Th. The research methods used in this research were desk studies, remote sensing imagery analysis, rock and soil radioactivity measurements, then integrating all data to obtain the distribution of U and Th in the area. Remote sensing is using Landsat-8 imagery with 15 m, 30 m, and 100 m spatial resolution which is recorded on July 23rd 2013. Geology of Mamuju and its surrounding were composed of volcanic rocks group and sedimentary rocks group. The group of volcanic rocks devided into Talaya volcanic complex and Adang volcanic complex. Volcanostratigraphy of Talaya volcanic complex consist of Khuluk Talaya, Gumuk Mambi, Gumuk Malunda, and Gumuk Kalukku. Volcanostratigraphy of Mamuju volcanic complex consist of Khuluk Mamuju, Gumuk Botteng, Gumuk Ahu, Gumuk Tapalang, Gumuk Adang, Gumuk Ampalas, Gumuk Sumare, and Gumuk Labuhan Ranau. The group of volcanic rocks consists of units of Talaya volcanic rocks, Malunda volcanic rocks, Adang volcanic rocks, Ampalas volcanic rocks, Sumare volcanic rocks, and Labuhan Ranau volcanic rocks. Meanwhile, group of sedimentary rocks consists of units of Sumare sandstone, Mamuju limestone, Tapalang limestone, Karampuang limestone, and alluvium. Radioactivity measurements of rock/soil were using gamma scintillation spectrometer model RS-125. The spectrometer was counting radioactivity dose rate and element concentration of K (%), eU (ppm), and eTh (ppm) from their radiation energy spectrum. Based on rock/soil radioactivity measurements, radioactivity dose rate in research area was ranging between 15 – 11,264.5 nSv/h with dose rate anomaly 1,693.6 nSv/h. Meanwhile, iv concentration of K element was ranging on 0 – 17.7%, eU 0 – 1,528.7 ppm, and eTh 1.3 – 826.4 ppm. Uranium content anomaly as much as 97.3 ppm eU was found in Mamuju River upstream, Botteng, Takandeang, and Ahu area. Thorium content anomaly as much as 369.5 ppm eTh was found in Takandeang, Pangasaan, Ahu, and Taan area. High content of of radioactive dose rate, K, U, and Th were found at phonolite and phonolite leucite rocks of Adang volcanic. High uranium content originates from davidite and thorianite as primary minerals, and also gummite and autunite as secondary minerals. Meanwhile, high thorium content originates from altered phonolite and phonolite leucite rock and their lateritic soil. Based on eU and eTh iso content maps, high content of eU and eTh were related to centers of Adang volcanic activity, especially crater and lava dome. Band ratio 4/2, 5/6, and 6/7 of Landsat-8 were showing imagery of iron oxide, ferromagnesian silicate, and hydroxyl clay distributions in research area. High content of U was distributed on phonolite and phonolite leucite rocks with less ferromagnesian silicate content, while Th distributions were not affected by the content of ferromagnesian silicate mineral. Uranium existence potencies were located in Mamuju River upstream, Takandeang, Ahu, Pangasaan, Botteng, and Taan area. Uranium and Thorium prospects were distributed only in Mamuju volcanic complex rocks.